Hub Angle Control for A Single Link Flexible Manipulator Based on Cuckoo Search Algorithm - aiman Azrael, Shaiful Nahar Sukri; Siti Sarah Zahidah, Nazri; Muhamad Sukri, Hadi; Annisa, Jamali; Hanim, Mohd Yatim; Intan Zaurah, Mat Darus (2021)
Flexible manipulators are one of the promising devices that can be applied in many fields especially in automation and manufacturing fields as they are designed to reduce energy consumption and increase the speed of operation. However, agitation process experienced in the complex structure of the system which causes unwanted vibration will affect the precision of operation. Thus, an efficient control system is required to make them functional. Therefore, the development of an accurate model of flexible manipulator was presented prior to establishing active vibration control to suppress the vibration and increase efficiency of the system. This paper presents the development of a Proportional-IntegralDerivative controller based on cuckoo search algorithm for a single link flexible manipulator system. Initially, the system was modelled using input and output experimental data of the hub angle. System identification was implemented via swarm intelligence algorithm known as cuckoo search algorithms based on auto regressive with exogenous model structure. Then, the performance of proposed algorithms was validated based on three robustness methods known as mean squared error, pole zero diagram stability and correlation tests. The simulation results showed superior performance of cuckoo search algorithm by achieving lowest mean squared error, good correlation tests and high root locus stability. Then, the cuckoo search model was implemented in the proposed control scheme with the aim of accurate positioning at the end point of flexible manipulator.